PENGARUH KEPEMIMPINAN TRANSAKSIONAL, TRANSFORMASIONAL, SITUASIONAL, VISIONER DAN PELAYAN DENGAN KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN BREBES - Karyono Karyono; Taofik Hidajat; Rahmi Yuliana (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aimed to determine the effect of transactional, transformational, situational, visionary and service leadership to Secretariat DPRD Brebes Regency employees’ performance. The population in this study is all employee of Secretariat DPRD Brebes Regency, as much 70 employees. Used sensus method, the sample in this study is all employee of Secretariat DPRD Brebes Regency as much 70 employees. This study used primary data and secondary data, followed by computer-assisted analysis of the multiple regression analysis IBM SPSSStatistics 19. The analysis showed that transactional, transformational, situational, visionary and service leadership have a positive influence to Secretariat DPRD Brebes Regency employees’ performance, partially and simultaneously. The coefficient of determination indicates that the transactional, transformational, situational, visionary and service leadership variable affect employees’ performance by 68,3%. Therefore, to improve Secretariat DPRD Brebes Regency employees’ performance, top manager must have competence about leadership style.